Adaptive Brain Shut-Down Counteracts Neuroinflammation in the Near-Term Ovine Fetus - Xu, Alex; Durosier, Lucien Daniel; Ross, Michael G.; Hammond, Robert; Richardson, Bryan S.; Frasch, Martin G. (Frontiers in Neurology, 2014)
Objective: Repetitive umbilical cord occlusions (UCOs) in ovine fetus leading to severe acidemia result in adaptive shut-down of electrocortical activity [electrocorticogram (ECoG)] as well as systemic and brain inflammation. We hypothesized that the fetuses with earlier ECoG shut-down as a neuroprotective mechanism in response to repetitive UCOs will show less brain inflammation and, moreover, that chronic hypoxia will impact this relationship. Methods: Near-term fetal sheep were chronically instrumented with ECoG leads, vascular catheters, and a cord occluder and then underwent repetitive UCOs for up to 4 h or until fetal arterial pH was <7.00. Eight animals, hypoxic prior to the UCOs (SaO2 <55%), were allowed to recover 24 h post insult, while 14 animals, 5 of whom also were chronically hypoxic, were allowed to recover 48 h post insult, after which brains were perfusion-fixed. Time of ECoG shut-down and corresponding pH were noted, as well as time to then reach pH <7.00 (ΔT). Microglia (MG) were counted as a measure of inflammation in gray matter layers 4–6 (GM4–6) where most ECoG activity is generated. Results are reported as mean ± SEM for p < 0.05. Results: Repetitive UCOs resulted in worsening acidosis over 3–4 h with arterial pH decreasing to 6.97 ± 0.02 all UCO groups’ animals, recovering to baseline by 24 h. ECoG shut-down occurred 52 ± 7 min before reaching pH <7.00 at pH 7.23 ± 0.02 across the animal groups. MG counts were inversely correlated to ΔT in 24 h recovery animals (R = −0.84), as expected. This was not the case in normoxic 48 h recovery animals, and, surprisingly, in hypoxic 48 h recovery animals, this relationship was reversed (R = 0.90). Conclusion: Adaptive brain shut-down during labor-like worsening acidemia counteracts neuroinflammation in a hypoxia- and time-dependent manner.